2008
DOI: 10.1007/s00535-007-2134-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 6381 hepatocellular carcinoma patients in southern Taiwan: prognostic features, treatment outcome, and survival

Abstract: This study, which considered untreated cases, missing data, and correlations between variables and official survival data sets, provides a large-scale comprehensive survival analysis. According to our results, high ALT and high AST/ALT were independent poor prognostic factors. Therefore, viral activity should be controlled in HCC patients, and patients with elevated AST/ALT ratios should be carefully monitored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
47
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 38 publications
8
47
0
Order By: Relevance
“…Moreover, as the prognostic value of baseline AST in HCC has been reported in previous studies, [19][20][21][27][28][29] our finding that this may be useful in predicting which CP-B patients are likely to derive benefit from sorafenib is intriguing, and suggests that further studies are warranted to evaluate the role of AST in clinical decision making in this setting. In summary, the findings reported here add to the growing body of evidence to suggest that sorafenib is effective in a broader patient population than was included in the Phase III studies; in particular patients with CP-B liver function.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Moreover, as the prognostic value of baseline AST in HCC has been reported in previous studies, [19][20][21][27][28][29] our finding that this may be useful in predicting which CP-B patients are likely to derive benefit from sorafenib is intriguing, and suggests that further studies are warranted to evaluate the role of AST in clinical decision making in this setting. In summary, the findings reported here add to the growing body of evidence to suggest that sorafenib is effective in a broader patient population than was included in the Phase III studies; in particular patients with CP-B liver function.…”
Section: Discussionmentioning
confidence: 58%
“…21 In addition, several studies have previously shown the prognostic relevance of baseline AST in patients with HCC. [19][20][21][27][28][29] In this study, the prevalence of baseline AST levels of ‡100 U ⁄ L in sorafenib-treated patients increased with advancing ChildPugh score, suggesting that elevated AST levels were reflective of liver cell damage due to progressive liver cirrhosis. Indeed, in CP-A patients, the median OS in patients with low (<100 U ⁄ L) baseline AST was about three times longer than that observed in patients with high ( ‡100 U ⁄ L) baseline AST, although, likely due to the small sample size, this failed to reach statistical significance (median OS 11.8 vs. 3.9 months respectively; P = 0.127) (Figure 1c).…”
Section: Discussionmentioning
confidence: 96%
“…It has been reported that high serum levels of ALT, AST, AFP and a high ratio of AST to ALT are highly associated with the progression of hepatocarcinogenesis in HCV or HBV-infected and liver cirrhosis patients (36)(37)(38)(39). In this study, we found the clinical serological markers ALT and AFP were associated with liver fibrosis in HCV-infected patients (p<0.05 and p<0.001, respectively), but AST was not associated (p=0.695).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the AFP expression is a marker of poor tumor biological behavior, poor liver function and a shorter overall survival time (39)(40)(41). Moreover, it was proved that elevated AFP levels were directly associated with more aggressive biological tumor activity (42), poor liver status with hepatitis or chronic cirrhosis (43) and a poor prognosis of HCC (44) for the Asian population.…”
Section: Discussionmentioning
confidence: 99%